2022
DOI: 10.1213/ane.0000000000006155
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection and Correction of Cerebral Desaturation With Noninvasive Oxy-Hemoglobin, Deoxy-Hemoglobin, and Total Hemoglobin in Cardiac Surgery: A Case Series

Abstract: Regional cerebral oxygen saturation (rSo 2 ) obtained from near-infrared spectroscopy (NIRS) provides valuable information during cardiac surgery. The rSo 2 is calculated from the proportion of oxygenated to total hemoglobin in the cerebral vasculature. Root O3 cerebral oximetry (Masimo) allows for individual identification of changes in total (ΔcHbi), oxygenated (Δo 2 Hbi), and deoxygenated (ΔHHbi) hemoglobin spectral absorptions. Variations in these parameters from baseline help identify the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Those will help in determining how sensitive changes in dP/dt are in detecting abnormal RV dysfunction. We have, however, reported that increases in dP/dt were clearly associated with improvement in RV function ( 32 , 47 , 48 )…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Those will help in determining how sensitive changes in dP/dt are in detecting abnormal RV dysfunction. We have, however, reported that increases in dP/dt were clearly associated with improvement in RV function ( 32 , 47 , 48 )…”
Section: Discussionmentioning
confidence: 94%
“…Those will help in determining how sensitive changes in dP/dt are in detecting abnormal RV dysfunction. We have, however, reported that increases in dP/dt were clearly associated with improvement in RV function (32,47,48) Supplemental digital content is available for this article. Direct URL citations appear in the printed text and are provided in the HTML and PDF versions of this article on the journal's website (http://journals.lww.com/ccejournal).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral (frontal cortex) rSO 2 is a global indicator of cerebral perfusion that reflects the balance between oxygen delivery and consumption. The measurement of cerebral Hb-oxygen saturation by means of NIRS is associated with important clinical outcomes [28] as it represents the proportion of O 2 Hb to tHb in the cerebral vasculature. Many clinical conditions such as hypotension and/or hypoperfusion, ischemia (caused by embolism), compression, or impairment of venous drainage may affect cerebral oxygenation, and in most of these situations, arterial Hb oxygen saturation (SaO 2 ) may remain within the normal limits.…”
Section: Transcranial Color-coded Duplex Doppler Sonographymentioning
confidence: 99%
“…Many clinical conditions such as hypotension and/or hypoperfusion, ischemia (caused by embolism), compression, or impairment of venous drainage may affect cerebral oxygenation, and in most of these situations, arterial Hb oxygen saturation (SaO 2 ) may remain within the normal limits. By examining rSO 2 and its sub-components (O 2 Hb, HHb, and tHb), the clinician can identify episodes of cerebral desaturation and intervene according to algorithms that have shown to successfully help improve cerebral oxygenation [28][29][30]. anterior cerebral artery (ACA), posterior cerebral artery (PCA), and communicating arteries (Fig.…”
Section: Transcranial Color-coded Duplex Doppler Sonographymentioning
confidence: 99%
“…Altogether, due to its non-invasive, continuous and easy to use character, cerebral oximetry alone may provide important information regarding tissue oxygenation in major surgery and in highrisk patients, especially when combined with a depth-of-anesthesia monitor 45 . Nevertheless, one should keep in mind that NIRS is a trend monitor and will not provide absolute tissue oxygenation values 2 .…”
Section: Lactatementioning
confidence: 99%